BEBAN JARINGAN SAAT MENGAKSES EMAIL DARI BEBERAPA MAIL SERVER - Thamrin, Husni (Komuniti: Jurnal Komunikasi dan Teknologi Informasi, 2011)
Expensive internet facilities require prudent in its use both as a source of information and communication media. This paper discusses observations of the perceived burden of network bandwidth when accessing some of the mail server using a webmail application. Mail server in question consists of three commercial server and 2 non-commercial server. Data when it download home page, while logged in, open the email, and during idle logout recorded with sniffer Wireshark. Observations in various situations and scenarios indicate that access Yahoo email gives the network load is very high while the SquirrelMail gives the network load is very low than 5 other mail servers. For an institution, use a local mail server (institutional) is highly recommended in the context of banddwidth savings.?